2001
DOI: 10.1074/jbc.c100436200
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of the Rotation of F1-ATP Synthase

Abstract: In F 1 -ATPase, the smallest known motor enzyme, unidirectional rotation of the central axis subunit ␥ is coupled to ATP hydrolysis. In the present study, we report the redox switching of the rotation of this enzyme. For this purpose, the switch region from the ␥ subunit of the redox-sensitive chloroplast F O F 1 -ATP synthase, which is located on the mitochondrial inner membranes, chloroplast thyalkoid membranes, and bacterial plasma membranes, synthesizes ATP, which is known as the universal energy "coin" in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…By using the newly designed chimeric complex (␣ 3 ␤ 3 ␥ redox ) in single molecule studies we successfully confirmed that oxidation of the redox region caused frequent long pauses (Fig. 6, C and D), which was consistent with a previous study (18). In addition, we observed that duration of rotation under oxidized conditions was relatively shorter than that shown under reduced conditions (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…By using the newly designed chimeric complex (␣ 3 ␤ 3 ␥ redox ) in single molecule studies we successfully confirmed that oxidation of the redox region caused frequent long pauses (Fig. 6, C and D), which was consistent with a previous study (18). In addition, we observed that duration of rotation under oxidized conditions was relatively shorter than that shown under reduced conditions (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…In a previous study we prepared a chmieric ␣ 3 ␤ 3 ␥ TCT complex originating from the thermophilic bacteria Bacillus PS3 and spinach chloroplast, and reported that oxidized ␣ 3 ␤ 3 ␥ TCT caused frequent long pauses (Ͼ 1 min) (14,18). However, we could not assign the origin of these long pauses to one of the sub-steps, 80°and further 40°(28), because the significantly modified chimeric mutants had insufficient angular resolution to allow for identification of sub-steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in higher plants the re-oxidation of CF 1 , following a light-dark transition, takes over 1 h, in the alga Dunaliella salina CF 1 is several times faster re-oxidized by a specific endogenous oxidant (14). Only recently redox modulation of the ␥ rotation has also been reported (15).…”
mentioning
confidence: 99%
“…A series of chimeras of F 1 with the FliJ-γ fusion rotor were prepared by substituting the C-terminal helix of FliJ with that of γ, to produce ChF 1 (xγ), where x indicates the length of substitution; x = 0, 9, 17, or 21. These chimeric complexes were expressed in E. coli and purified with Ni 2+ -affinity chromatography (Qiagen) followed by size-exclusion chromatography with Superdex 200 10/300GL (GE Healthcare) as previously reported (33). The purified enzymes were biotinylated at the two cysteines in the FliJ sequence and subjected to rotation analysis.…”
mentioning
confidence: 99%